2009
DOI: 10.1007/s12562-009-0069-1
|View full text |Cite
|
Sign up to set email alerts
|

Extractive components and taste aspects of fermented fish pastes and bean pastes prepared using different koji molds as starters

Abstract: Extractive components and taste aspects of fermented fish pastes and bean pastes prepared using different koji molds as starters Abstract We have evaluated four commercially available mold starters (SP-01, NY, M1, and ''for kome miso'') for fermented fish pastes with the aim of determining the effect of different koji molds on the nutritional and sensory characteristics of the fermented product. Comparative studies among different fermented fish and bean pastes were also conducted. Protein contents were consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…The presence of compounds that are precursors of the flavoring compounds, as well as suitable medium conditions, are necessary. In our previous studies [1,2], biochemical analysis of miso prepared from both soybeans and fish meat revealed that both comprise a large number of substrates that are similar in composition or have similar properties; however, the major difference between them is the difference in raw materials and/or a different metabolic capacity of the enzymes derived through koji fermentation by A. oryzae. Our investigation on the enzyme activity of koji during fermentation indicated that enzyme activity in koji is high, especially protease and amylase activity.…”
Section: Hypothetical Pathways For the Enzymatic Activity Leading To mentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of compounds that are precursors of the flavoring compounds, as well as suitable medium conditions, are necessary. In our previous studies [1,2], biochemical analysis of miso prepared from both soybeans and fish meat revealed that both comprise a large number of substrates that are similar in composition or have similar properties; however, the major difference between them is the difference in raw materials and/or a different metabolic capacity of the enzymes derived through koji fermentation by A. oryzae. Our investigation on the enzyme activity of koji during fermentation indicated that enzyme activity in koji is high, especially protease and amylase activity.…”
Section: Hypothetical Pathways For the Enzymatic Activity Leading To mentioning
confidence: 99%
“…Fish miso is a low-fat food, and ripened miso contains around 1% lipids (wet mass) [2]; however, the small amount of fat in miso is important for the development of the typical flavor during the fermentation process. Flavoring compounds such as thiazoles, sulfur-containing compounds, esters, aldehydes, alcohols, and ketones are mostly present in the lipid phase of ripened fermented pastes [35].…”
Section: Catabolic Products Of Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…16) To minimize the effect of the moisture content, salt content and pH value on the SPME extraction, identical values of the foregoing parameters to those of the experimental sample (fish miso) reported earlier were taken into account. 1,2) However, while comparing the recovery for the extraction of added 1-octen-3-ol between the identical solution and fish miso, an important matrix effect was apparent for fish miso which greatly reduced the adsorption of analytes in the liquid phase of the fiber. The matrix effect of a complex substrate on the volatile isolation through SPME fiber can be explained by complex competition among the analytes due to the difference in partial pressure of the volatile analytes in the headspace.…”
Section: Effect Of Different Matrices On the Isolation Of Volatile Comentioning
confidence: 99%
“…Our previous investigations have revealed its nutritional and taste aspects. 1,2) However, characterizing the volatiles and standardizing the volatile analysis for this newly developed flavor-rich food product have not previously been carried out. The volatiles are normally present at low concentrations of mgl À1 or less and should therefore be determined by such sensitive analytical techniques as gas chromatography (GC) with flame ionization detection (FID), mass spectrometry (MS) or olfactrometry (O).…”
mentioning
confidence: 99%